Necessity and ways to improve the systems of irrigation management on a resource basis (Моделювання, керування та інформаційні технології, 2025)
The necessity and ways of improving irrigation management systems are considered. An analysis of international and native experience in the development and implementation of information systems to support management decision-making in irrigation has been carried out. The current changes in conditions and requirements to irrigated agricultural production are described. Primarily in terms of the critical shortage and increasing cost of water and energy resources, which necessitate the improvement of existing methods and means of water use planning for irrigation on a resource basis. Appropriate resource-based solutions are proposed.